SATUAN TUGAS PENATAAN LAHAN DAN INVESTASI UNTUK KEPASTIAN BERUSAHA DALAM PERTAMBANGAN - Istianti, Ria; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Abstract: In order to organize mining management, the President carries out a land management policy by evaluating and dividing mining land. The President's order, Presidential Regulation 70 of 2023, on land allocation for investment management, is thought to be a remedy for the problem of managing mineral and metal mining regulations. Consequently, we need to check whether the Regulation is in line with the Mineral and Coal Mining Law 4 of 2009, as revised by the Determination of Government Regulations 6 of 2023 (in lieu of Law 2 of 2022, which dealt with job creation) before it became law. The investigation found that the Mineral and Coal Law, which deals with the distribution of mining management responsibilities to community groups, and Presidential Regulation No. 70 of 2023, which deals with land allocation for investment management, are at odds with one another. The research uses normative juridical methods.Keywords: Mining, Management, License